Cultural self-efficacy of baccalaureate nursing students in a Greek University - Malliarou, Maria; Sarafis, Pavlos (My University, 2013)
Background: Culturally specific care requires that nursing students know, understand, and identify cultural factors related to client care, and conduct their nursing practice accordingly. The aim of this study was to identify the cultural self-efficacy of baccalaureate nursing students in a Greek University. Materials and Methods: In this cross-sectional study, a Transcultural Self-Efficacy Tool was used as a framework, to examine transcultural practices of Greek nursing students. A questionnaire was administered to a sample of students at a Greek Nursing Faculty, and 136 questionnaires returned (Response Rate: 87%). Results: Neither group, i.e., freshmen and senior (4th) year students of a Greek Nursing Faculty, expressed confidence in their ability to care for culturally-diverse patients. Mean scores for the three subscales were higher for senior students (cognitive m = 7.17, practical m = 6.76, affective m = 7.77) than for freshmen students (cognitive m = 6.96, practical m = 6.60, affective m = 7.43) making year of studies a characteristic that was found to be statistically important. A medium level of self-efficacy was found for the two subscales; cognitive (72%, n = 39; 78%, n = 62), practical (52%, n = 26; 48.8%, n = 4), and for the affective subscale the level of self-efficacy was found high (78%, n = 39; 82.6%, n = 71) in freshmen year and senior students. Conclusions: Results suggest that freshmen students exhibited a lack of confidence asking patients from different cultural backgrounds, questions about their own cultural heritage and beliefs while senior students appreciated cultural sensitivity and awareness and therefore confirmed the value of skilled nursing care.
Keywords: Culture; Greece; Nursing; Self-efficacy; Students; University